Reasons for delay in timely administration of adjuvant chemotherapy for patients with stage III colon cancer: a multicentre cohort study from the McGill University Department of Oncology. Issue 1 (8th March 2021) - Elkrief, Arielle; Redstone, Genevieve; Petruccelli, Luca; Ali, Alla'a; Thomas, Doneal; Fernandez, Myriam; Rousseau, Caroline; Aleynikova, Olga; Anderson, Dawn; Ghitulescu, Gabriela; Vasilevsky, Carol-Ann; Dalfen, Richard; et al.
Abstract : Purpose: Adjuvant chemotherapy within 56 or 84 days following curative resection is globally accepted as the standard of care for stage III colon cancer as it has been associated with improved overall survival. Initiation of adjuvant chemotherapy within this time frame is therefore recommended by clinical practice guidelines, including the European Society for Medical Oncology. The objective of this study was to evaluate adherence to these clinical practice guidelines for patients with stage III colon cancer across the Rossy Cancer Network (RCN); a partnership of McGill University's Faculty of Medicine, McGill University Health Centre, Jewish General Hospital and St Mary's Hospital Center. Patients and methods: 187 patients who had been diagnosed with stage III colon cancer and received adjuvant chemotherapy within the RCN partner hospitals from 2012 to 2015 were included. Patient and treatment information was retrospectively determined by chart review. Χ 2 and Wilcoxon rank-sum tests were used to measure associations and a multivariate Cox regression model was used to determine risk factors contributing to delays in administration of adjuvant chemotherapy. Results: The median turnaround time between surgery and adjuvant chemotherapy was 69 days. Importantly, only 27% of patients met the 56-day target, and 71% met the 84-day target. Increasing age, having more than one surgical complication and being diagnosed between 2013–2014 and 2014–2015 reduced the likelihood that patients met these targets. Furthermore, delays were observed at most intervals from surgery to first adjuvant chemotherapy treatment. Conclusion: Our study found that within these academic hospital settings, 27% of patients met the 56-day target, and 71% met the 84-day target. Delays were associated with hospital, surgeon and patient-related factors. Initiatives in quality improvement are needed in order to improve adherence to recommended treatment guidelines for prompt administration of adjuvant chemotherapy for stage III colon cancer.